49.7k views
5 votes
Plz solve this if u know plz​

Plz solve this if u know plz​-example-1
User ItayAmza
by
5.4k points

2 Answers

3 votes

Answer:

- 3

Explanation:

Using the rules of exponents/ radicals


a^{(m)/(n) }
\sqrt[n]{a^(m) }


a^(-m)
(1)/(a^(m) )

Thus


64^{(1)/(3) } =
\sqrt[3]{64} = 4


64^{-(1)/(3) } =
(1)/(4)


64^{(2)/(3) } =
\sqrt[3]{64^(2) } = 4² = 16

Substituting values into the given expression


(1)/(4) (4 - 16)

=
(1)/(4) × - 12

= - 3

User James Bruckner
by
5.7k points
3 votes

Solution:


{64}^{ - (1)/(3) } ( {64}^{ (1)/(3) } - {64}^{ (2)/(3) } ) \\ {64}^{ (1)/(3) - (1)/(3) } - {64}^{ (2)/(3) - (1)/(3) } \\ {64}^(0) - {64}^{ (1)/(3) } \\ 1 - \sqrt[3]{64} \\ 1 - 4 \\ - 3

Answer:


- 3

User Adam Bittlingmayer
by
5.5k points